1967
DOI: 10.1677/joe.0.0380013
|View full text |Cite
|
Sign up to set email alerts
|

The Action of Oxytocin and Synthetic Analogues on the Isolated Mammary-Gland Myoepithelium of the Lactating Rat; Effect of Some Ions

Abstract: The contractile response of mammary-gland strips from lactating rats to oxytocin varied with the concentration of calcium ions in the organ bath; calcium could be partially substituted by strontium but not by magnesium. High concentrations of potassium did not substantially affect the response to oxytocin. In these and several other respects the mammary gland myoepithelium resembles uterine smooth muscle, notwithstanding the differences in morphology and embryonal origin.The effects of 12 synthetic analogues o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1968
1968
1997
1997

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 18 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…Moore et al [15] reported that myoepithelial cells in the tissue of mammary glands failed to contract in the presence of oxytocin after a 30-min incubation in a Ca 2+ -free solution at 37°C. Polácek et al [20] reported that mammary tissue strips contracted in response to oxytocin in a Ca 2+free solution, but that the response gradually decreased and disappeared upon further incubation in the same solution. In our study, oxytocin induced the contraction even 30 min after perfusion in the Ca 2+ -free solution, although the amplitude of the Ca i 2+ increase was reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Moore et al [15] reported that myoepithelial cells in the tissue of mammary glands failed to contract in the presence of oxytocin after a 30-min incubation in a Ca 2+ -free solution at 37°C. Polácek et al [20] reported that mammary tissue strips contracted in response to oxytocin in a Ca 2+free solution, but that the response gradually decreased and disappeared upon further incubation in the same solution. In our study, oxytocin induced the contraction even 30 min after perfusion in the Ca 2+ -free solution, although the amplitude of the Ca i 2+ increase was reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Both protected intermediates and that of [Gly7]oxytocin4 were converted to the disulfide-bridged cyclic peptides and the products purified by methods described previously.10,14 '15 The pharmacological properties of [Gly7]oxytocin, [Thr4,Gly7]oxytocin, and hydroxy[Thr4,Gly7]oxytocin were evaluated by methods previously described16™18 and by assays on isolated strips of rat mammary gland. 19…”
mentioning
confidence: 99%
“…In the lactating guinea-pig (Bisset, 1964) methyloxytocin, like oxytocin, increases milk-ejection pressure. It also contracts the mammary gland strip in vitro, but the rate of contraction is slower than with oxytocin and the onset of tachyphylaxis is more rapid; with ethyloxytocin these anomalies become more pronounced (Polacek et al, 1967). On the mammary gland, carbamoyl-methyloxytocin, though it invariably inhibits the response to oxytocin, does retain some remnants of oxytocin-like activity.…”
Section: Discussionmentioning
confidence: 99%
“…A strip 3 cm x 0 5 cm x 0 5 cm was suspended in a 10 or 12-5 ml organ bath at 380 C containing Tyrode's solution: (mM) NaCl 137, KC1 217, NaHCO3 11 9, NaH2PO 0-42, CaCl2 0 9-1P8, MgCl2 0-1'0, glucose 5-6, gassed with a mixture of 95% oxygen and 5% carbon dioxide. Before use, the strip was stored overnight in Tyrode's solution at 40 C. Tension was recorded isometrically by the same method as that used for the isolated uterus or with a Briiel-Kjaer strain-gauge and recorder (Polacek, Krejci & Rudinger, 1967). An initial tension of 400-500 mg was applied and the tissue allowed to equilibrate for 1-2 h before use.…”
mentioning
confidence: 99%